(untitled) (Journal of Oriental Studies, 2021)
Oral communicative competence is the core ability for second language learners to conduct daily communication. In order to get close to the current situation of spoken Chinese teaching in the classrooms of indigenous Kazakhstan people, this survey takes the Chinese classroom of the International Kazakh-Chinese Language College as a case study. Mainly using interviews and naturalistic observation of classroom, this study examined not only the teaching practices but also the concepts and attitudes of the teachers and students in the school regarding the teaching of spoken Chinese and the development of oral communicative competence. The paper discussed several defects of the spoken Chinese teaching in the school in four dimensions: teacher quality, textbook resources, teaching methods, as well as testing and assessment. According to the general situation of Chinese language teaching in Kazakhstan, the reasons for these problems are analyzed in the context and suggestions for improvement are put forward. Key words: Kazakhstan, Chinese language, oral teaching in classroom